United States, Meade River Coal Mine office in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Entrance to Mead River Coal Mine office. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3